Analysis of outcomes in resected early-stage NSCLC with rare targetable driver mutations - Nadia Ghazali; Jamie Feng; Katrina Hueniken; Khaleeq Khan; Karmugi Balaratnam; Thomas K. Waddell; Kazuhiro Yasufuku; Andrew Pierre; Laura Donahoe; Elliot Wakeam; Marcelo Cypel; Jonathan Yeung; et al. (Therapeutic Advances in Medical Oncology)
Background: Given advancements in adjuvant treatments for non-small-cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK)-targeted therapies, it is important to consider postoperative targeted therapies for other early-stage oncogene-addicted NSCLC. Exploring baseline outcomes for early-stage NSCLC with these rare mutations is crucial. Objectives: This study aims to assess relapse-free survival (RFS) and overall survival (OS) in patients with resected early-stage NSCLC with rare targetable driver mutations. Methods: This retrospective single-center study identified stage I–III NSCLC patients with rare targetable mutations who underwent curative surgery. Tissue-based molecular profiling identified mutations in KRAS G12C, EGFR Exon20, Erb-B2 receptor tyrosine kinase 2 ( ERBB2 ), ALK , ROS1 , B-Raf proto-oncogene ( BRAF ) V600E, mesenchymal–epithelial transition factor ( MET ) exon14 skipping, and rearranged during transfection ( RET ). Baseline patient and tumor characteristics, mutation subtype, and TP53 co-mutation were correlated with RFS and OS using Cox regression. The KRAS G12C cohort was used as the reference for survival comparisons. Results: Among 225 patients, mutations included the following: KRAS G12C ( n  = 101, 45%), MET exon 14 skipping ( n  = 26, 12%), EGFR Exon 20 ( n  = 25, 11%), ERBB2 ( n  = 25, 11%), ALK fusion ( n  = 16, 7%), ROS1 fusion ( n  = 14, 6%), BRAF V600E mutation ( n  = 13, 6%), and RET fusion ( n  = 5, 2%). Five-year survival probabilities were 76% for stage I, 60% for stage II, and 58% for stage III. RFS was shorter across most mutation subgroups compared to KRAS G12C, with ROS1 mutations showing significantly poorer RFS (HR 2.70, p  = 0.019). By contrast, all mutation subgroups were associated with better OS than KRAS G12C. The incidence of brain metastasis was highest in ERBB2 (22% at 5 years). TP53 co-mutation was associated with significantly worse OS (HR 2.35, p  = 0.008). Conclusion: While RFS was poorer for most mutations compared to KRAS G12C, OS generally was better, suggesting a potential role for postoperative targeted therapies. These findings warrant further investigation through prospective studies and clinical trials to optimize adjuvant treatment strategies for patients with early-stage NSCLC harboring rare driver mutations.